Evidence of household transfer of ESBL-/pAmpC-producing Enterobacteriaceae between humans and dogs – a pilot study - Oskar Ljungquist; Ditte Ljungquist; Mattias Myrenås; Cecilia Rydén; Maria Finn; Björn Bengtsson (Infection Ecology & Epidemiology, 2016)
Background: Extended-spectrum cephalosporin-resistant Enterobacteriaceae (ESCRE) are an increasing healthcare problem in both human and veterinary medicine. The spread of ESCRE is complex with multiple reservoirs and different transmission routes. The aim of this study was to investigate if ESCRE carriage in dogs is more prevalent in households with a known human carrier, compared to households where humans are known to be negative for ESCRE. Identical ESCRE strains in humans and dogs of the same household would suggest a possible spread between humans and dogs. Methods: Twenty-two dog owners with a positive rectal culture for ESCRE each collected a rectal sample from their dog. In addition, a control group of 29 healthy dog owners with a documented negative rectal culture for ESCRE each sampled their household dog. Samples were cultivated for ESCRE using selective methods. In households where both humans and dogs carried ESCRE, isolates were further analysed for antimicrobial susceptibility by disc diffusion or microdilution and for genotype and genetic relatedness using molecular methods. Results: In 2 of 22 households studied, identical ESCRE strains with respect to bacterial species, antibiogram, genotype, and MLVA type were found in humans and dogs. The ESCRE found in the two households were ESBL-producing E. coli with the resistance gene blaCTX-M-27 and AmpC-producing E. coli with blaCMY-2, blaTEM-1. ESCRE were not found in dogs in the control group. Conclusions: In households where humans are carrying ESCRE, identical strains were to a limited extent found also in household dogs, indicating a transfer between humans and dogs. In contrast, ESCRE were not found in dogs in households without human carriers.